2020
DOI: 10.37434/tpwj2020.05.03
|View full text |Cite
|
Sign up to set email alerts
|

Problems and prospects of surfacing of copper and copper parts by wear-resistant layers (Review)

Abstract: subscriptions 12 issues per year, back issues available. $384, subscriptions for the printed (hard copy) version, air postage and packaging included. $312, subscriptions for the electronic version (sending issues of Journal in pdf format or providing access to IP addresses). Institutions with current subscriptions on printed version can purchase online access to the electronic versions of any back issues that they have not subscribed to.Issues of the Journal (more than two years old) are available at a substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Surface treatment can improve the performance of materials at an affordable cost to bring about functional properties that would otherwise not be provided by the substrate material. Since surface engineering [Berndt 2020] can improve the performance of these materials at a lower cost, it has tremendous potential to provide technological solutions to various engineering problems. Surfacing with hard wear-resistant materials [Kartsev 2020] is intended to increase the wear resistance of sealing, rubbing, and other surfaces of parts operating under conditions of metal-to-metal friction in corrosive media (acid, alkali, salt, and organic solvent) [Panda 2014[Panda , 2018a[Panda ,b, 2019Valicek 2016& 2017, Macala 2009& 2017, Pandova 2018, Krenicky 2012, high and low temperatures, and/or pressure [Bozek 2021].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface treatment can improve the performance of materials at an affordable cost to bring about functional properties that would otherwise not be provided by the substrate material. Since surface engineering [Berndt 2020] can improve the performance of these materials at a lower cost, it has tremendous potential to provide technological solutions to various engineering problems. Surfacing with hard wear-resistant materials [Kartsev 2020] is intended to increase the wear resistance of sealing, rubbing, and other surfaces of parts operating under conditions of metal-to-metal friction in corrosive media (acid, alkali, salt, and organic solvent) [Panda 2014[Panda , 2018a[Panda ,b, 2019Valicek 2016& 2017, Macala 2009& 2017, Pandova 2018, Krenicky 2012, high and low temperatures, and/or pressure [Bozek 2021].…”
Section: Introductionmentioning
confidence: 99%
“…The research [Sadeghi 2019] includes a substantive discussion of high-temperature corrosion mechanisms, new coating formulations, and a brief comparison of corrosion-resistant coatings obtained using various thermal surfacing techniques. It is suggested that with a careful and reasonable choice of technique and technology of surfacing, as well as compliance with a certain temperature range of pre-and associated heating of parts, it will be possible to obtain a high-quality connection of wear-resistant layers of alloys based on iron, nickel or cobalt [Miglierini 2004, Babinets 2020, Pollak 2020a. Scientific researches [Zhu 2018, Pereplotchikov 2018 suggests that the best indicators of wear resistance are achieved due to the formation of microstructures in the surfacing material that corresponds to the Charpy principle: individual solid inclusions with a low coefficient of friction and a low tendency to scuffing are located in a plastic matrix.…”
Section: Introductionmentioning
confidence: 99%